The influence of complex motor activities on the morphofunctional and psychoemotional state of elderly people from different countries of Europe and Asia - Aleksander Skaliy; Tatiana Skaliy; Tursynzada Kuangaliyeva; Zhaxat Kenzhin; Asanalieva Meergul; Sławomir Letkiewicz (Kharkiv State Academy of Physical Culture, 2024)
Background and Study Aim. The World Health Organization has recognized that insufficient physical activity is a serious public health problem. A large number of studies are devoted to improving livelihoods and increasing life expectancy of the population through the formation of guidelines for a healthy lifestyle. Regular physical activity is one of the most important components of maintaining health and healthy aging. Many European countries already have well-developed social programs to support physical activity among older people. This includes the organization of sporting events, financial support for clubs for seniors, as well as infrastructure that promotes an active lifestyle (active parks, walking and cycling paths, a sufficient number of swimming pools, etc.). Therefore, the purpose of the study was to identify the effectiveness of complex motor training on the morphofunctional and psycho-emotional state of elderly people from different countries of Europe and Asia. Material and Methods. The study involved 240 (30 men and 30 women each from Poland, Kazakhstan, Kyrgyzstan and Ukraine) elderly people (the average age of the study participants was 68.24±3.01 years). The groups were homogeneous in age, gender, social status, interests, level of physical fitness, functionality and motivation. The study participants followed a developed physical activity program for older people. Classes lasted a year, 3 times a week, lasting 60 minutes each. The program included theoretical and practical parts. Theoretical material concerned the benefits of physical activity, motor mode and dosage of exercise for older people. The practical part included the most common types of physical education and health activities among older people (swimming, Nordic walking, health tourism). The study involved assessing the morphofunctional state of older people by determining body mass indexes, functional changes and Robinsonal, as well as the Skibinsky and Rufier tests, and the assessment of well-being, activity and mood (WAM) was carried out using a questionnaire Results. During the study, we measured morphofunctional indicators and determined the psycho-emotional state of elderly people from Poland, Kazakhstan, Kyrgyzstan and Ukraine, who were engaged in a developed program using various types of physical activity, namely: swimming, Nordic walking, health tourism Conclusions. The results obtained indicate the effectiveness of using a comprehensive physical activity program among older women and men from different countries of Europe and Asia. All participants showed positive changes in all indicators. Minor changes over the course of a year of training according to the developed program in the indicators of the morphofunctional and psycho-emotional state of elderly people from Poland indicate that a healthy lifestyle is being popularized in the European Union country and conditions are being created for regular physical activity of the population, including older people.